(untitled) (Plant Bulletin, 2025)
The wilt disease of sesame (Sesamum indicum L.) caused by Fusarium oxysporum is one of the most significant fungal diseases that affect yield production. In this study, two different approaches, namely in vivo and in vitro, were focused on, in which different microbiological and plant-based antagonists were investigated after 3, 5, and 7 days of incubation to inhibit the development of F. oxysporum in sesame. The results of this study revealed great varietal differences in the growth inhibition of F. oxysporum at all growth stages. In in vitro studies, Bacillus subtilis was more effective in growth inhibition (98.67%) of F. oxysporum among the bacterial antagonists. In fungal antagonists, Aspergillus niger showed a great potential of maximum inhibition in mycelium growth (92.43%) and in plant-based antagonists, Cannabis sativa exhibited maximum antifungal activity (85.5%) as compared to control. However, the highest bacterial antagonistic activity was evaluated comparatively to fungal and plant-based antagonists. Whereas, in vivo, the study showed the highest antifungal activity (38% - 69%) of selected fungal antagonists, followed by plant-based antagonists (34.17% - 65%) and bacterial antagonists (20% - 48%). This study would help the agrochemical companies to develop microbial and plant-based fungicides that are non-phytotoxic and eco-friendly for the management of fungal diseases, as compared to chemical fungicides that are harmful to consumers and pollute the environment.